The form of street spatial layout based on a wind environmental perspective - X.Y. Ying; Q. Kan; G. Ding (Lowland Technology International, 2018)
With China's rapid urbanization, the construction of central areas in city with numerous buildings and dense population has greatly changed the microclimate. Different street spatial layouts change the internal wind environment, which affect the pedestrian comfort. Computational fluid dynamics (CFD) models are used to study the correlation between the three-main street spatial layout factors, which are near-line rate, street interface density and street aspect ratio, under the simulation of relevant weather conditions. Firstly, the wind speed within the street change with the increase of the near-line rate like a parabola trend, and the wind speed reaches its peak about at a near-line rate of 70%. In that case, it’s conducive to ventilation. Secondly, with the reduction of street interface density the variation of the wind speed of each measuring point in the streets is getting bigger and bigger, and the pedestrian walking in them will feel the change of wind speed which makes the comfort of pedestrian decrease. Thirdly, the average wind speed in urban streets is inversely proportional to the street aspect ratio. These conclusions will provide an important reference and evaluation basis for urban designers at the beginning of design and effectively avoid future wind environment problems.